A practical technique combining orbicularis oculi muscle resection-based epicanthoplasty and orbicularis-tarsus fixation double-eyelid plasty for cosmetic blepharoplasty. Issue 12 (December 2019) - Sun, Weiyi; Yin, Ningbei; Song, Tao; Wu, Di; Li, Haidong; Wang, Yongqian
Summary: Background: A plump single eyelid with medial epicanthal fold is the morphological feature of the East Asian population. This study describes a practical technique that combines orbicularis oculi muscle resection-based epicanthoplasty and orbicularis-tarsus fixation double-eyelid plasty for cosmetic blepharoplasty and reports on surgical outcomes in a large number of Chinese patients. Methods: For supratarsal crease formation, the soft tissue was removed in a conservative manner and the orbicularis oculi muscle was anchored on the tarsus to build a reliable attachment. To correct the epicanthal fold, a modified redraping technique was used for the design of skin incision, and most importantly, a triangular muscle block composed of the orbicularis oculi muscle was selectively removed to release the abnormal tension in the epicanthal fold. Results: From January 2015 to February 2019, 475 patients underwent double-eyelid blepharoplasty combined with epicanthoplasty using this technique. The follow-up period ranged from 2 to 38 months, with a mean period of 16 months. Of these, 97% of the patients were satisfied with surgical outcomes, presenting well-defined palpebral folds and naturally improved inner canthus contour, with no conspicuous scar. The photographic analysis in 84 patients showed significant improvement in palpebral fissure proportion postoperatively. No supratarsal crease drooping or recurrence of the epicanthal fold was observed up to 38 months after the surgery. Conclusions: This method is a safe and reliable technique to achieve an elongated and more balanced eye shape in Chinese patients, with minimal scarring and a low risk of postoperative complication in a long follow-up period.